A NEW GENUS OF ECTRICHODIINAE FROM POINT CALIMERE SOUTHERN INDIA (HETEROPTERA : REDUVIIDAE) - LIVINGSTONE, DAVID; MURUGAN, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
A new reduviid genus namely Synectrychotes of sub-family Ectrichodiinae has been described from Southern India. The types species Synectrychotes callimerei has beed described and illustrated. Distant (1904 & 1910) while describing the various genera of the subfamily Ectrichodiinae, considered the number of joints of antennae as a primary character for diagnosis of the various genera and on that basis the maximum of eight joints and minimum of four joints have been recognised in the various genera of Ectrichodiinae. Though antennal segmentation could be considered as a reliable criterion for the taxonomy of this subfamily, Cook (1977) did not attach any importance to it. Instead, she considered the length of the rostral segments as a primary criterion. However, Distant's division of the subfamily Echodiinae on the basis of antennal characters still has its value and therefore that character has been adopted for the present diagnosis. The genus Ectrychotes alone has both eight segmented antennae as well as the intermediate spinous angulation of the scutellum. The other three genera having eight segmented antennae include Audernacus, Bayerus and Scadra. The present genus, as described below, resembles Ectrychotes in having eight segmented antennae, but differs from it by the absence of the median apical spinous angulation of the scutellum and in that respect it resembles the other three genera.